2005
DOI: 10.3141/1908-09
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Red Light Running Crashes Based on Quasi-Induced Exposure and Multiple Logistic Regression Method

Abstract: According to recent national statistics, red light running crashes represent a significant safety problem at signalized intersections. To examine the overall characteristics of red light running crashes, this study used the 1999 to 2001 Florida crash database to investigate the crash propensity related to traffic environments, driver characteristics, and vehicle types. The quasi-induced exposure concept and multiple logistic regression technique were used to perform this analysis. The results showed that traff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
1
10
1
Order By: Relevance
“…Coefficients of Age 2_10 and Age are 0,177 and −0,143, which are significant with p-value less than 0,001. According to calculation it is not most likely to have severe mountainous freeway crashes when the driver age is about 40 and that is to say both older and younger drivers are more likely to be involved in severe crashes, which is consistent with the study of Yan et al [27]. That is because younger drivers have less driving experiences and older drivers' bodies are not as strong as those of the middle-aged.…”
Section: Binary Logistic Regressionsupporting
confidence: 77%
“…Coefficients of Age 2_10 and Age are 0,177 and −0,143, which are significant with p-value less than 0,001. According to calculation it is not most likely to have severe mountainous freeway crashes when the driver age is about 40 and that is to say both older and younger drivers are more likely to be involved in severe crashes, which is consistent with the study of Yan et al [27]. That is because younger drivers have less driving experiences and older drivers' bodies are not as strong as those of the middle-aged.…”
Section: Binary Logistic Regressionsupporting
confidence: 77%
“…That means that there were a different number of RLR violations due to different vehicle categories, similar found by Huang and Chin (2009). Considering the total number of vehicles in traffic flow and number of RLR violation in each particular vehicle category, it could be concluded that the most dangerous vehicle category is passenger cars, comparing to Yan et al (2005) where truck drivers have higher red-light violation rate. One of the most important goals for decision-makers due to RLR is to reduce the total number of RLR, maybe the second or the third goal is to reduce RLR rates.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, Wu et al (2012) have found that cyclists often made RLR at the beginning and at the end of red phase. Yan et al (2005) highlighted that there are correlation between accidents happened on traffic light intersection and data such as: drivers age (the youngest drivers have the highest red-light violations rate), drivers type (truck drivers have high red-light violation rate), intersection type (Y-shaped intersections have a higher percentage of violations), etc. Besides, average traffic flow speeds, traffic volume rate, the green split, the number of through and crossing lanes, signal coordination, vehicle's approaching speed, driver's age and gender, etc, are also contributing factors that have important influence on driver's decision at intersections (Liu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, af Wahlberg (2009) has commented on the high subjectivity of culpability determination, although accepting its use as an exposure surrogate where nonculpable drivers can be shown to reflect a random sample of the overall population. Still, the method has continued to be used in a number of studies comparing risk for different categories of road users (Haque, Chin & Huang, 2008;Huang & Chin, 2009;Voas, Tippetts, Romana, Fisher & Kelley-Baker, 2007;Yan, Radwan & Birriel, 2005) and some confirmation of its underlying tenets has been claimed (Chandraratna & Stamatiadis, 2009). …”
Section: Introductionmentioning
confidence: 95%